Apoio pedagógico, ação coletiva e diálogo: tramas da formação continuada em educação inclusiva - Oliveira, Luzia de Fátima Medeiros de (2006)
This work detaches the importance of the continued formation of the educators in terms of the inclusive educational process, pointing as basic elements the continued formation of the educational professionals. In this direction, it points and it defends the dialogue in the perspective of David Bohm, with interfaces of the freireanas ideas, as a methodological resource of action that allows the organization of strategies of collective and effective pedagogical support in inclusive schools, in the same time articulates the continued formation of the professionals in education. Characterized as research in a dialogical action with collective participation and collaboration, it counted with the participation of 87 educators, between professors, pedagogical, managing coordinators and specialists of special education in two schools of the state and municipal public system of Natal/RN. The results had pointed with respect to the viability of the dialogue as articulated methodological tool of the continued formation in service, when providing the establishment of personal and professional relationship between the educators, favoring the discursive enjoyment of the lived experiences, allows the organization of strategies of collective and effective pedagogical support in the scholar environment. On the basis of these results, this work also points to some items to reflections as the reorganization of the Secretariats and the schools, in the direction to brighten up the fragmentation and the discontinuity of the pedagogical actions evidenced and to instigate a process of changes that has glimpsed the professional development of the educators through its continued formation in service and the improvement of the school in the way of the concretization of an education directed toward the acceptance, respect and attendance the diversity of its pupils, as detaches the official documents and the studies on the inclusive education